2021
DOI: 10.1212/nxi.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinal Layer Thickness With Cognition in Patients With Multiple Sclerosis

Abstract: ObjectiveRetinal layer thickness (RLT) measured by optical coherence tomography (OCT) is considered a noninvasive, cost-efficient marker of neurodegeneration in multiple sclerosis (MS). We aimed to investigate associations of RLT with cognitive performance and its potential as indicator of cognitive status in patients with MS by performing generalized estimating equation (GEE) analyses.MethodsIn this cross-sectional study, patients with at least mild signs of cognitive impairment were examined by OCT as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…While within the OCTiMS trial, no robust association between retinal layer thinning and performance in SDMT could be demonstrated, and a recently published study observed an association between attention and executive function tests and retinal layer thickness. 17,31 Despite some advantages of GCIPL over pRNFL and more pronounced effects in EDSS than in SDMT prognostication, the findings of the present study demonstrate that the prognostic value to predict disability progression still prevails after a long-term follow-up of approximately 6 years. This prognostic potential is based on (1) smaller values of baseline thickness of retinal layers and (2) higher annual thinning rates of retinal layers.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…While within the OCTiMS trial, no robust association between retinal layer thinning and performance in SDMT could be demonstrated, and a recently published study observed an association between attention and executive function tests and retinal layer thickness. 17,31 Despite some advantages of GCIPL over pRNFL and more pronounced effects in EDSS than in SDMT prognostication, the findings of the present study demonstrate that the prognostic value to predict disability progression still prevails after a long-term follow-up of approximately 6 years. This prognostic potential is based on (1) smaller values of baseline thickness of retinal layers and (2) higher annual thinning rates of retinal layers.…”
Section: Discussioncontrasting
confidence: 57%
“…While within the OCTiMS trial, no robust association between retinal layer thinning and performance in SDMT could be demonstrated, and a recently published study observed an association between attention and executive function tests and retinal layer thickness. 17,31…”
Section: Discussionmentioning
confidence: 99%
“…Such a future study could also integrate potential other measurements of disease progression, that were not assessed in this work. These might include cognitive tests such as the Symbol Digits Modality Test (SDMT), spinal lesions in MRI or other new imaging modalities like optical coherence tomography [Baetge et al, 2021]. As clinical measures of disease progression have limitations, finding a suitable fluid biomarker that could help identify patients at risk of long-term worsening appears even more pressing.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that subclinical ganglion cell loss during MS might result—in addition to subclinical optic neuropathy—from retrograde transsynaptic degeneration and might be a measure for chronic CNS neurodegeneration [20‐22]. In line with this concept, GCIP thinning has been shown to correlate with both brain and spinal cord atrophy and disability in patients with MS [23‐29]. Similar associations have been reported in individuals with CIS and radiologically isolated syndrome [13,28,30,31].…”
Section: Discussionmentioning
confidence: 82%